(untitled) (Jurnal Teknologi (Sciences & Engineering), 2013)
The use of technology in teaching and learning is not a new phenomenon in the field of e-learning including its use for learning Arabic. This is evidenced through several research attempts and works done on learning through technology which is consistent with the existence of and access to a more effective, interesting and dynamic technology. Virtual learning, or also known as 'virtual learning environment' (VLE), is a teaching and learning platform that is designed to enhance students' learning experience through computer and internet. This article discusses the potential of a virtual learning platform towards learning Arabic through the development of EZ-Arabic as an alternative and interactive virtual platform for students to learn Arabic in primary schools. The design and development of EZ-Arabic prototype is using 'rapid prototyping' instructional design (ID) model which is proposed by Tripp and Bichelmeyer (1990) after conducting needs analysis of content and determining objectives. After the completion of the prototype development, a small-scale session of trying out with users was conducted through the social networking site FacebookÂ® for two weeks from 15 February to 1 March 2012. Usersâ€™ feedbacks and suggestions were compiled for it to be utilized in the next phase of installation and maintenance in designing the prototype. Qualitative findings were then collected that include 55 comments and suggestions from users with 48 'LIKES'. Qualitative findings of the proposed improvements and upgrades have been analyzed into seven (7) main themes that related to the web interface, application supports, challenges and distractions, material compatibility, usability, value-added and diversity, and content of syllabus.